Carabodes azoricus - Nunes, Rui (2021)
JUSTIFICATION: Carabodes azoricus is an endemic species of the Azores (Portugal), having been described from one location in Terceira island. From the species' description, it potentially has a very small Extent of Occurrence (4 km²) and Area of Occupancy (4 km²), but these are likely underestimates, as this species probably has a wider distribution through the soil component of the island. It can be assumed that this species is affected by human activities and invasive plant species, which alter the natural structure and composition of the soil. Future climatic changes and increased risk of droughts will also affect this species. The present situation of this species needs to be further assessed and further research is needed into its population, distribution, threats, ecology and life history. Conservation of natural habitats and invasive species control could potentially aid this species conservation. Based upon the incomplete knowledge regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).